2011
DOI: 10.1136/bmjqs-2011-000187
|View full text |Cite
|
Sign up to set email alerts
|

Health professional networks as a vector for improving healthcare quality and safety: a systematic review

Abstract: BackgroundWhile there is a considerable corpus of theoretical and empirical literature on networks within and outside of the health sector, multiple research questions are yet to be answered.ObjectiveTo conduct a systematic review of studies of professionals' network structures, identifying factors associated with network effectiveness and sustainability, particularly in relation to quality of care and patient safety.MethodsThe authors searched MEDLINE, CINAHL, EMBASE, Web of Science and Business Source Premie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
202
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 225 publications
(218 citation statements)
references
References 80 publications
8
202
0
8
Order By: Relevance
“…The results suggest that the coordination and sharing of information among physicians through a communication network could have a positive impact on enhanced quality of care and health of patients. The findings are consistent with the conclusion of Cunningham et al (30), which showed that integrated communication networks among specialists could promote the coordination and quality of health care services to patients. Additionally, such networks could help identify weaknesses and shortcomings related to the healthcare provided to the patients.…”
Section: Discussionsupporting
confidence: 82%
“…The results suggest that the coordination and sharing of information among physicians through a communication network could have a positive impact on enhanced quality of care and health of patients. The findings are consistent with the conclusion of Cunningham et al (30), which showed that integrated communication networks among specialists could promote the coordination and quality of health care services to patients. Additionally, such networks could help identify weaknesses and shortcomings related to the healthcare provided to the patients.…”
Section: Discussionsupporting
confidence: 82%
“…This is also congruent with the literature on networks where effective networks have a compelling organising purpose (Cunningham et al, 2011;Malby et al, 2013). This is reflected in responses from the present study where LIQH is seen as more than simply a fluidly organised model that can be used as-and-when:…”
Section: Key Lessons From the Literature For Liqhsupporting
confidence: 79%
“…Participating in formal education outside the workplace and extending professional networks may be effective in enhancing learning and EBP. In a review, Cunningham et al (2011) showed that effective professional networks contributed to the quality of care and patient safety through efficient transmission of information and social and professional interaction within and across networks.…”
Section: Individual Aspects Of Learning and Evidencebased Practicementioning
confidence: 99%